2006
DOI: 10.1111/j.1365-2133.1994.tb08505.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous slack skin: report of a case associated with Hodgkin's disease and a review of the literature

Abstract: Summary We report a case of granulomatous slack skin (GSS) associated with Hodgkin's disease, and review the literature on this entity. GSS, a variant of cutaneous T‐cell lymphoma, clinically presents with erythematous patches in the flexures, which gradually transform into bulky, pendulous areas of skin. Histology shows an elastolytic granulomatous infiltrate, with atypical lymphoid cells, and occasional epidermotropism. As far as we are aware, 10 cases of GSS, including our patient, have been reported in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 6 publications
1
18
1
3
Order By: Relevance
“…131,134 Systemic involvement has been reported rarely, occurring in the lymph nodes, spleen, and submucosa of the bronchial tree. 127,131,140,141 Differential diagnosis. The differential diagnosis of granulomatous slack skin includes middermal elastolysis, acquired cutis laxa, and granulomatous cutaneous T-cell lymphoma.…”
Section: Granulomatous Slack Skinmentioning
confidence: 99%
“…131,134 Systemic involvement has been reported rarely, occurring in the lymph nodes, spleen, and submucosa of the bronchial tree. 127,131,140,141 Differential diagnosis. The differential diagnosis of granulomatous slack skin includes middermal elastolysis, acquired cutis laxa, and granulomatous cutaneous T-cell lymphoma.…”
Section: Granulomatous Slack Skinmentioning
confidence: 99%
“…Some authors claimed that GSS was a benign disorder, and a variant of cutaneous T-cell lymphoma [4]. In contrary, some authors suggested that GSS was a precursor of malign lymphoma, especially Hodgkin's disease [7,10,14,15]. However, in the literature, 58% of cases had not been associated with any lymphoproliferative malignancy.…”
Section: Discussionmentioning
confidence: 88%
“…Ulcerações ocorrem eventualmente. 6,7 O caso aqui descrito apresentava localização cutânea preferencial e esplenomegalia, sem evidência de doença em outros sítios anatômicos.…”
Section: Relato Do Casounclassified
“…Os achados mais proeminentes dessa doença incluem a perda dos tecidos reticular e elástico da derme e células gigantes multinucleadas com fagocitose das fibras elásticas. 1,2,6,9 Nas lesões tardias, observa-se infiltrado linfocitário, localizado na derme e no tecido celular subcutâ-neo. 1 Células linfóides com epidermotropismo também são observadas, e microabscessos de Pautrier podem ser encontrados.…”
unclassified
See 1 more Smart Citation